ROLE OF VIRECHANA IN PSORIASIS (KITIBHA KUSHTA) – A CASE STUDY (AYUSHDHARA, 2020)
Psoriasis is a common chronic, recurrent, autoimmune disease of the skin and joints. It can have a significant negative impact on the physical, emotional and psychosocial well-being of affected patients. The use of modern medicine has greatly improved psoriasis treatment by providing symptomatic relief. However, some individuals fail to respond to treatment or lose initial efficacy, and it may be difficult to find the optimal treatment for these patients. Also, modern medicines have their own side effects in long course.The Ayurvedic diagnosis is considered as Kitibhakushta, which is a Vata-kapha predominant Kushta. Here, an effort was made to treat a forty-nine years old male diagnosed with long standing moderate to severe erythrodermic psoriasis who had received systemic therapies in modern medicine without sufficient response previously, by classical Ayurvedic regimen.As the principle of treatment of all types of Kushta is Samshodhana along with Samshamana drugs, in this study, Virechana was given followed by which Samshamana drugs were given for 30 days. Assessment of skin lesions were done at the end of treatment.